2013
DOI: 10.1371/journal.pone.0083543
|View full text |Cite
|
Sign up to set email alerts
|

Overweight People Have Low Levels of Implicit Weight Bias, but Overweight Nations Have High Levels of Implicit Weight Bias

Abstract: Although a greater degree of personal obesity is associated with weaker negativity toward overweight people on both explicit (i.e., self-report) and implicit (i.e., indirect behavioral) measures, overweight people still prefer thin people on average. We investigated whether the national and cultural context – particularly the national prevalence of obesity – predicts attitudes toward overweight people independent of personal identity and weight status. Data were collected from a total sample of 338,121 citizen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 45 publications
4
81
0
Order By: Relevance
“…In the last three decades, social scientists and public health researchers have consistently documented anti-fat discrimination in the U.S. and European countries (Chen and Brown 2005;Crandall and Schiffhauer 1998;Flint and Snook 2014;Greenberg et al 2003;Puhl, Andreyeva, and Brownell 2008;Puhl and Heuer 2009). Not thoroughly studied quantitatively yet, South Korea also serves as a useful case study of weight discrimination with its extremely high level of weight stigma against big body sizes (Jung and Lee 2006;Marini et al 2013;Schwekendiek, Minhee, and Ulijaszek 2013).…”
Section: Anti-fat Discriminationmentioning
confidence: 99%
“…In the last three decades, social scientists and public health researchers have consistently documented anti-fat discrimination in the U.S. and European countries (Chen and Brown 2005;Crandall and Schiffhauer 1998;Flint and Snook 2014;Greenberg et al 2003;Puhl, Andreyeva, and Brownell 2008;Puhl and Heuer 2009). Not thoroughly studied quantitatively yet, South Korea also serves as a useful case study of weight discrimination with its extremely high level of weight stigma against big body sizes (Jung and Lee 2006;Marini et al 2013;Schwekendiek, Minhee, and Ulijaszek 2013).…”
Section: Anti-fat Discriminationmentioning
confidence: 99%
“…This theorized relationship is based almost entirely on analysis of data drawn from the US, Western Europe, and Australia, especially undergraduate college student samples. With the rise of overweight/obesity as a common aspect of contemporary human biology, and the concurrent rise of anti‐obesity public health efforts, weight stigma is globalizing (e.g., Brewis, Wutich, Falletta‐Cowden, & Rodriguez‐Soto, 2011; Marini, et al, 2013). Yet, we do not know if weight stigma might also exert significant influence on stress‐related health outcomes outside of the Anglosphere ( cf .…”
Section: Introductionmentioning
confidence: 99%
“…Our study relating weight and weight concern to depression is focused on South Korea due to its recent identification as possibly the most explicitly weight‐stigmatizing of all nations (Marini, Sriram, Schnabel, Maliszewski, Devos, Ekehammar, … Schnall, 2013). According to the OECD report on obesity (2014), while obesity rates remain comparatively very low in South Korea (2% in 1995 and 4% obese in 2011), overweight is on the increase overall (23% in 1995 and 28% overweight in 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, these results indicate that potentially we are seeing less stigma as weight increases. Although this contradicts research indicating that overweight people hold the same level of weight bias as non-overweight people it does support the finding that even though overweight people do display weight bias it is a weaker relationship than that found in nonoverweight people (Marini et al, 2013;Schwartz et al, 2008). Further examination of this finding is crucial, due to the negative influence of weight bias (as detailed in Chapter 2).…”
Section: Implications and Future Directionsmentioning
confidence: 62%
“…Similarly, showed that there was no difference between average-weight and overweight participants in their levels of explicit or implicit weight bias. Unlike many other groups, then, overweight people do not have a bias towards their own group (although they may have weaker anti-fat bias than average-weight people, see Marini et al, 2013). Instead, both overweight and average-weight people are prejudiced against overweight people.…”
Section: Negative Attitudes Towards Overweight Peoplementioning
confidence: 99%